The prevalence of muscoskeletal disorder and associated ergonomic risk factors among secondary school teachers - Hemawathy, Sandran (2022)
The purpose of thesis is to study the relationship between ergonomic risk factors and muscoskeletal disorders among the secondary school teachers in Damansara, Kuala Lumpur. The ergonomic risk factors chosen for this study are body posture and length of Visual Display Unit Usage. The risk factors mentioned were evaluated on how it impacted the muscoskeletal disorders among the teachers. To meet the research objectives, descriptive and quantitative method is used in this study. The questionnaire was slightly modified using Standardized Nordic Questionnaire (SNQ) to evaluate pain on the neck, shoulder, hand, and elbow, upper and lower back pain and the data were analysed using SPSS software version 28. 125 respondents out of 150 teachers responded to the questionnaire. Based on the findings, it shows higher prevalence MSD rate among the secondary school teachers at Damansara, Kuala Lumpur with the mean of 3.46 (past 12 months) and 3.60 (past 7 days) respectively. There is a significant relationship between body posture and duration of length usage of VDU with MSD. Teachers have complained pain of right elbow (44.8%), neck (38.4 %) and right shoulder (37.6%). The awareness level of ergonomics and MSD among secondary school teachers in Damansara is poor, hence, appropriate ergonomic control measures, educational programs and prevention of work related muscoskeletal disorder are recommended for the school organization in order to reduce the MSD cases and to enhance work efficiency.